Evaluasi Proses Bisnis Pelayanan Akademik Skripsi menggunakan FILKOM Apps pada Fakultas Ilmu Komputer Universitas Brawijaya (FILKOM UB) dengan Metode Quality Evaluation Framework (QEF) - Adilla Widyandhana Nuriman; Nanang Yudi Setiawan; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
FILKOM APPS is the system that support in FILKOM academic service, include in thesis. But in reality, there are problems in implementation, so it will make some troubles for the student as the users of this service. The problem is one with others student can't get verification from academic after the student upload their proposal at the same time. The other problem is student can't get letter of assignment in the same time with the other student. This problem will make impact for process research of their thesis especially for student of final semester. So, it need an evaluation business process for academic service in thesis using FILKOM APPS with quality evaluation framework (QEF) method. The Quality Evaluation Framework (QEF) have some dimension to measure the quality of time service. First step for researcher is modelling the business process base on event log in FILKOM APPS record especially in thesis service with data extraction from Disco tools and the automatically process business modelling with ProM 6.8 tools. Next step with heuristic method, the event log data will modelled automatically. After that we do some mapping for business process modelling from event log and operational standard procedure. After that, researcher do some evaluation with time efficiency matric. The result of this evaluation are the activity of publishing of letter of assignment, verification from academic study program, verification proposal document after P0 and the scheduling of result presentation with this percentage of those activity not reach 100%.